A retrospective analysis of setup and intrafraction positional variation in stereotactic radiotherapy treatments. Issue 12 (3rd November 2020) - Barnes, Micah; Yeo, Adam; Thompson, Kenton; Phillips, Claire; Kron, Tomas; Hardcastle, Nicholas
Abstract: Purpose: The aim of this study was to provide a comprehensive assessment of patient intrafraction motion in linac‐based frameless stereotactic radiosurgery (SRS) and radiotherapy (SRT). Methods: A retrospective review was performed on 101 intracranial SRS/SRT patients immobilized with the Klarity stereotactic thermoplastic mask (compatible with the Brainlab frameless stereotactic system) and aligned on a 6 Degree of Freedom (DoF) couch with the Brainlab ExacTrac image guidance system. Both pretreatment and intrafraction correction data are provided as observed by the ExacTrac system. The effects of couch angle and treatment duration on positioning outcomes are also explored. Results: Initial setup data for patients is shown to vary by up to ±4.18 mm, ±2.97°, but when corrected with a single x‐ray image set with ExacTrac, patient positions are corrected to within ±2.11 mm, ±2.27°. Intrafraction patient motion is shown to be uniformly random and independent of both time and couch angle. Patient motion was also limited to within approximately 3 mm, 3° by the thermoplastic mask. Conclusions: Our results indicate that since patient intrafraction motion is unrelated to couch rotation and treatment duration, intrafraction patient monitoring in 6 DoF is required to minimize intracranial SRS/SRT margins.